1994
DOI: 10.1002/1097-0142(19940201)73:3<534::aid-cncr2820730307>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein–producing gastric carcinoma with enteroblastic differentiation

Abstract: Background. Alpha‐fetoprotein (AFP) is a useful tumor marker for hepatoma and yolk sac tumor. Recently, elevations of serum AFP were reported in patients with other malignancies, especially gastric cancers. Two distinct tumor morphologies, hepatoid and clear cell, have been correlated with AFP production. Methods. Two patients with AFP‐producing gastric carcinoma were evaluated with immunohistochemical, ultrastructural, and biochemical studies. Results. In Patient 1, the primary and metastatic carcinomas consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 16 publications
(1 reference statement)
4
91
0
Order By: Relevance
“…Meanwhile, Kinjo et al classified them, according to the characteristic of tumor, as a common adenocarcinoma type, enteroblastic type, hepatoid type, and yolk sac tumor type [3]. The fetal gastrointestinal type and enteroblastic type were considered to be equivalent to carcinoma with enteroblastic differentiation [15]. However, AFP-producing esophageal carcinoma, including adenocarcinoma with enteroblastic differentiation, has not been categorized by the World Health Organization (WHO) classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Kinjo et al classified them, according to the characteristic of tumor, as a common adenocarcinoma type, enteroblastic type, hepatoid type, and yolk sac tumor type [3]. The fetal gastrointestinal type and enteroblastic type were considered to be equivalent to carcinoma with enteroblastic differentiation [15]. However, AFP-producing esophageal carcinoma, including adenocarcinoma with enteroblastic differentiation, has not been categorized by the World Health Organization (WHO) classification.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, adenocarcinoma with enteroblastic differentiation has a primitive intestinal-like structure, composed of cuboidal or columnar cells with clear cytoplasm [1,3,15]. In case of stomach location, the gastric mucosal epithelium was covered with tubular adenocarcinoma, and the deeper part of the mucosal layer and the submucosa were composed of tubular adenocarcinoma and adenocarcinoma with enteroblastic differentiation [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, gastric cancer with clear cell change is not always associated with AFP-producing GC, with 14.5% (9 of 62) of clear cell GCs showing AFP positivity. 39 Clear cell changes have been reported in 74% (17 of 23) of AFPproducing GCs 40 and in 36% (36 of 101) of glypican-3-expressing GCs.…”
Section: Gastric Adenocarcinoma With Clear Cell Changementioning
confidence: 99%
“…AFP is a major plasma protein produced by the yolk sac and the liver during fetal life. AFP expression in adults is often associated with hepatoma or teratoma 19 . This study showed that, ENA was negative for AFP no indication was observed undifferentiated cell proliferation.…”
mentioning
confidence: 99%